1999
DOI: 10.1023/a:1006978431521
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Reactive oxygen species (ROS) are implicated in the pathogenesis of stress-induced gastrointestinal mucosal injury. In the present study, we have investigated the effects of acute and chronic stress on the enhanced production of ROS including superoxide anion [SA; as determined by cytochrome c reduction (CCR)] and hydroxyl radicals (OH), and correlated the enhanced production of these free radicals with increased lipid peroxidation, membrane microviscosity and DNA fragmentation, indices of oxidative tissue dam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(15 citation statements)
references
References 0 publications
0
14
0
1
Order By: Relevance
“…Compared to it, the Yang's [9] correlation shows marked improvement. A modified equation was suggested by Bagchi et al ., [10] wherein the solid loading ratio and Archimedes number were recognized as significant variables. Acceleration length correlations were also proposed by Wang et al .…”
Section: Introductionmentioning
confidence: 99%
“…Compared to it, the Yang's [9] correlation shows marked improvement. A modified equation was suggested by Bagchi et al ., [10] wherein the solid loading ratio and Archimedes number were recognized as significant variables. Acceleration length correlations were also proposed by Wang et al .…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that treatment of mice with thalidomide prior to the admin- 34 istration of ethanol dose-dependently reduced the gastric ulcer index. Thalidomide pretreatment 35 significantly reduced the levels of pro-inflammatory cytokines [tumor necrosis factor (TNF)-a, interleukin 36 (IL)-1b, IL-6], malondialdehyde (MDA) and myeloperoxidase (MPO) activity. In addition, thalidomide 37 significantly inhibited ethanol-induced nitric oxide (NO) overproduction in gastric tissue.…”
mentioning
confidence: 99%
“…[29][30][31] Since GSPE also contain high amount (84%) of proanthocyanidins, antioxidant activities of proanthocyanidins might contribute to the antinociceptive effect of GSPE. In fact, this notion is supported also by the observation that Croton celtidifolius extract containing high amount of proanthocyanidins (75%) exhibited antinociceptive effect in the formalin test.…”
Section: Discussionmentioning
confidence: 99%